2003
DOI: 10.1063/1.1582831
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical evaluation of hydrogen storage capacity in pure carbon nanostructures

Abstract: Carbon nanotubes have been proposed as promising hydrogen storage materials for the automotive industry. By theoretical analyses and total-energy density functional theory calculations, we show that contribution from physisorption in nanotubes, though significant at liquid nitrogen temperature, should be negligible at room temperature; contribution from chemisorption has a theoretical upper limit of 7.7 wt %, but could be difficult to utilize in practice due to slow kinetics. The metallicity of carbon nanotube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
168
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(174 citation statements)
references
References 33 publications
5
168
1
Order By: Relevance
“…119, 2376 ͑2003͔͒, Li et al concluded from a series of calculations and analysis that ''when compared to other pure carbon nanostructures, we find no rational reason yet why carbon nanotubes should be superior in either binding energies or adsorption/ desorption kinetics'' for H 2 storage. 1 This is in contrast to our encouraging computational data and analysis on H 2 storage in single walled carbon nanotubes ͑SWNT͒ 2 which Li et al largely dismissed, while urging others to perform further calculations to resolve the issues raised.…”
contrasting
confidence: 51%
“…119, 2376 ͑2003͔͒, Li et al concluded from a series of calculations and analysis that ''when compared to other pure carbon nanostructures, we find no rational reason yet why carbon nanotubes should be superior in either binding energies or adsorption/ desorption kinetics'' for H 2 storage. 1 This is in contrast to our encouraging computational data and analysis on H 2 storage in single walled carbon nanotubes ͑SWNT͒ 2 which Li et al largely dismissed, while urging others to perform further calculations to resolve the issues raised.…”
contrasting
confidence: 51%
“…Density functional theory calculations show that at room temperature hydrogen adsorption in SWNT cannot exceed 7.7 wt.% even when contributions from chemisorption of hydrogen on carbon are considered [173]. Assuming only physisorption of hydrogen in CNTs, it would be impossible to achieve this amount of adsorption at room temperature.…”
Section: Carbon and Carbon-based Nanostructuresmentioning
confidence: 99%
“…Current estimations of the optimal binding energy for adsorption of hydrogen at ambient temperature and considering safe delivery pressure conditions of 1.5 − 30 bar, amount to ∼ 0.2 eV/molecule [102][103][104]. Meanwhile, kinetic effects may be critical for practical applications (e.g., complete H 2 storage-release cycles must be realized within seconds) and when these are taken into account favourable binding energies turn out to be ∼ 0.7 eV/molecule [105]. Based on these assessments, the binding energy range that typically is targeted in most ab initio H 2 -storage works is 0.1 − 1.0 eV/H 2 , which spans from dispersion to moderately covalent molecule-GAM interactions (see Table I).…”
Section: H2 Storagementioning
confidence: 99%